Investigation of spectroscopy remote sensing for mapping pavement systems condition - Tsiripillos, Elias (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
An investigation of spectroscopy remote sensing for mapping pavement systems conditions is undertaken in this research. Spectral data were acquired by the HR1024 spectroradiometer and were analysed, processed and interpreted. A spectral library was developed in order to define the attributes of the different pavement systems. This research has plot the spectral profiles of each pavement system that are investigated and found that the older roads have high reflectance and the areas with the deformations or cracks can be identified as they have lower reflectance than the un-cracked – healthy areas. Several t – test were applied followed the spectral profiles in order to indicate whether there is a difference in the means between the pavement systems. After the t – test, Pearson correlation coefficient and Euclidean distance were used in order to observe wavelengths that are going to be used in the spectral experiment. Through the spectral experiment these wavelengths were used in a try to identify cracked areas or deformations. The results of the spectral experiment have shown that the cracked areas or deformations are not visible in the wavelengths.
Keywords: Spectroscopy; Remote sensing